Clinical study to compare the effect of intratympanic injection of lidocaine and dexamethasone in tinnitus of cochlear origin - ., Surabhiraj; Megalamani, Somanath B.; Gadag, Raveendra P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Due to various aetiologies and the less known mechanism involved in tinnitus no treatment modality gives consistent results. Here, we are comparing the efficacy of intratympanic injections of lidocaine and dexamethasone. Methods: Out of 100 selected patients, consecutive patients who fulfilled the inclusion and exclusion criteria are randomly allocated into one of the 2 study groups (50 members each). Intratympanic injection of lidocaine and dexamethasone are given to respective group weekly for 3 consecutive weeks and response is assessed at 1 month and 2nd month of injection. Results: In our study, maximum patients were in the age group of 56-65 yrs. When the effect of lidocaine and dexamethasone on tinnitus (based on THI-tinnitus handicap inventory questionnaire) is compared, dexamethasone is found to be more efficacious than lidocaine with a p value<0.005. Out of total, 96% of dexamethasone group and 68% of lignocaine group have got improved THI score during second follow up. While assessing the effect of lidocaine and dexamethasone on pure tone audiogram (PTA) it is found that, dexamethasone is showing more improvement when compared to lignocaine (p value<0.05). Regarding the adverse effects of injection, side effect is more with lidocaine (50%) than that of dexamethasone (36%), most common adverse effect which we came across was burning type of pain, followed by giddiness which last only for few seconds. Conclusions: Dexamethasone is effective in reducing the overall THI score hence reduces handicap when compared with that of lidocaine with added advantage on hearing.